Study Pengaruh Campuran Bahan Bakar Premium Dan Ethanol Terhadap Unjuk Kerja Mesin Motor Bensin Empat Langkah - Muryanto, Edy, Ir.Sunardi Wiyono, MT, Amin Sulistyanto, ST (2016)
Issues of fossil fuels which surfaced in recent years is the problem of depletion of fossil fuels and global warming. This time is considered very important to continue the efforts of observation and the development of alternative fuel technologies. With high levels of alcohol can be used directly on the machine , or can be mixed with a certain level in gasoline as fuel. Utilization of alcohol as a fuel substitute for gasoline , pertamax , pertalite or as a mixture of petrol is expected to reduce fuel consumption of petroleum. This study aims to determine the effect of using a mixture of gasoline and ethanol and the corresponding fuel type and to obtain engine performance 4 stroke petrol engine optimum exhaust emissions and determine the level of fuel consumption. The results of this study indicate that the fuel by using a variation of premium fuel or a mixture of premium variation and ethanol ( 5 % , 10 % , 15 % , 20 % ) there is a change of characteristics, namely an increase in power up to 7000 rpm rotation. At high rotation , the addition of ethanol is able to provide more torque compared to when using premium fuel. On the exhaust emissions are also the highest value of CO concentration on premium fuel and 20% ethanol. At 7000 RPM HC gas concentrations have decreased in all variations of the fuel was 286 ppm. And the smallest value HC concentration in the exhaust gas is at a premium fuel and 20% ethanol. At 7000 rpm at 155 ppm.